Audience practicies of the tv series consumption - A. B. Mishustina, (Ukrainian Cultural Studies, 2019)
The article is devoted to the analysis of the audience practices of the TV series as a type of visual culture of Postmodern. Parameters of the transformation of Modern visual practices in the context of the series presenting as a culture industry and their role in changing the anthropological model are considered. The significance of the consumption of TV series as a type of postmodern cultural industry, which produces a human as a TV series-viewer, is postulated. Such visual means of the serial industry as spoilers, suspense, Easter eggs, which are producing postmodernist types of visual interactivity, are revealed. Appealing to the basic concepts of postmodernist philosophy allows the author to research the following transformations of the audience practices connected to the TV series: fragmentation as opposed to a consistent and complete system as a modern form of hierarchy, speaking out against the conventional authorities – the "death of the author", irony, equal game-like participation of both authors and consumers.The basic characteristics of Postmodern culture are represented by an analysis of the works of such authors as U. Eko, I. Hasan, T. Adorno and M. Horkheimer, Z. Bauman, J. Baudrillard, S. Lash, F. Jameson, M. Foucault, P. Bourdieu, J. Liotard. The study of the series is a productive area of scientific research in the field of humanitarian knowledge as foreign (J. Mittell, M. Fleisfeder, M. Voitin, V. Kurinny, A. Khitrov, K. Pevzner, O. Akopov, N. Zakharchenko, I. Tuzovsky, Y. Belenkiy), as well as domestic (M. Sobutsky, L. Voznesensky, and others) researchers who consider this concept in various aspects.Postmodern, producing a new cultural product – a series, and even the production of a new cultural industry for the production of serials is not only limited to the industrialization of culture, but is carried out as a culture of industry – the viewer of the series is produced as a postmodern anthropological model. In this way, the "social implosion" is carried out – since the type of production of the new anthropological model does not become discursive and disciplinary practices (purely social instruments of human production, that is, a direct type of influence of a person on the person, or only through the medium of knowledge), and their own cultural anthropologies of anthropology are formed. models as a (global) cultural industry (the series itself).
Keywords: TV series, Postmodern, visual studies, audience practices, consumption, culture industry